The luck of the Irish : how a shipload of convicts survived the wreck of the Hive to make a new life in Australia - Smith, Babette, 1942- (Allen & Unwin, 2014)
The author of the bestselling Cargo of Women and Australia's Birthstain tracks the lives of Irish convicts who arrived in Australia the mid-1800s, uncovering a long-lasting influence of the Irish convicts on our national character.